Misinterpretasi Mahasiswa pada Representasi Histogram dan Box Plot - Intan Sari Rufiana; Wahyudi Wahyudi; Dwi Avita Nurhidayah (Universitas Muria Kudus, 2020)
Mathematical representation is the center of mathematics learning. However, is the student's ability to interpret the form of representation good? In this study, we adapted multiple choice questions from the LOCUS assessment to describe how 30 semesters III students interpreted the bar chart and box plot. The students answered this multiple choice question by including the reasons. The results showed that 50% of the 30 students gave correct responses regarding the boxplot. These fifteen students stated that the box plot cannot be used to calculate a lot of data. However, these 15 students were unable to come up with reasons why the box plot could not be used to calculate a lot of data. The remaining 50% of students stated that other diagrams such as scatter plots, histograms and bar charts cannot be used to calculate a lot of data, but box plots can be used to calculate the amount of data. As many as 40% of students are not able to distinguish a bar chart from a histogram. They assumed that qualitative data could be described using a histogram instead of a bar chart. The results of this study are explained by the dual-process theory.